Convenience behavior in German university students is associated with sociodemographic, study- and health-related factors - Schwab, Lisa; Reichel, Jennifer L.; Werner, Antonia M.; Schäfer, Markus; Heller, Sebastian; Edelmann, Dennis; Beutel, Manfred E.; Letzel, Stephan; Dietz, Pavel; Simon, Perikles; Kalo, Kristin (Frontiers in Public Health, 2024)
Background: The transition from school to university is often accompanied by a change in students' lifestyles. So far little is known whether convenience behavior is an essential factor affecting students' health and social interaction. In a heterogeneous population regard to sociodemographic and anthropometric characteristics the Convenience Behavior Questionnaire (CBQ) showed a better relationship between convenience-related behavior with overweight and obesity than established questionnaires. Here we assessed convenience behavior in a large well characterized cohort of university students and its association with health-related (mainly sedentary behavior and physical activity), study-related and sociodemographic factors with the Convenience Behavior Questionnaire (CBQ). Methods: A total of 4,351 students participated in an online survey, of which 3,983 (23.6±5.3 years old, 71.3% females) answered the questions concerning convenience behavior. A low value in the CBQ indicates more convenience behavior (Convenience Behavior Index (CBI) range: 3 -15). Differences with regard to sociodemographic (age, gender, body mass index), study-related (semester, degree, field of study) and health-related (physical activity, sedentary behavior) variables were examined with Mann-Whitney-U test or Kruskal-Wallis test and post hoc tests (Bonferroni).Results: The CBI of men and women differed significantly (z = -6.847, p < .001, r = .11). Firstyear students and students beyond their first year showed significant differences (z = -2.355, p ≤ .05, r = .04). Differences were also found in the field of study (Chi2 (6) = 147.830, p < .001) and the targeted degree (Chi2 (7) = 79.985, p < .001). Furthermore, differences were found in the body mass index (Chi2 (5) = 70.678, p < .001), physical activity (Chi2 (2) = 279.040, p < .001) and sedentary behavior (z = -4.660, p < .001, r = .07).The results showed risk groups of convenience behavior among students (men, first-year, students enrolled in "Science, Technology, Engineering and Mathematics (STEM)", bachelor). Our results confirm for the first time in a very homogeneous population a gender difference and an association between CBI and health-related factors. Further studies are needed to analyze the health behavior of students in more detail, especially their convenience behavior.